From self-awareness to divine connection: Relational and culturally grounded transpersonal development in islamic boarding school - Arina Mufrihah; Arini Elya Nura Hanun (Academic Journal of Psychology and Counseling, 2026)
The epistemological gap between indigenous spiritual guidance and transpersonal counseling leaves the construct of barakah uncharted in pesantren pedagogy. This creates a twofold conceptual-empirical gap that isolates local practices from global discourse, necessitating a theoretical bridge to frame barakah as a legitimate orientation for psycho-spiritual growth. This study explores barakah as the ultimate aim of transpersonal maturation in pesantren. Utilizing focused ethnography with 15 participants (Kiai, Nyai, alumni, and students), the study finds that barakah manifests as Transcendental Actualization. This process operates through a relational psycho-spiritual anchor (sanad) and teacher-student inner resonance that regulates internal energy. Barakah functions as a corrective force fostering inner watchfulness (muraqabah) and a surplus of meaning (ziyadatul khair) within a communal ecology of mercy. It catalyzes a transition toward theocentric agency through trust (tawakkul) and integrated patience-gratitude. This research contributes an indigenous Islamic transpersonal counseling framework, emphasizing the counselor's role as Murabbi for holistic well-being.